On some developments in investigation of groups with prescribed properties of generalized normal subgroups - Kirichenko, V.V.; Kurdachenko, L.A. (Algebra and Discrete Mathematics, 2010)
The survey is dedicated to investigation of groups with prescribed properties of generalized normal subgroups. The roots of such investigations lie in the works by R. Dedekind, R. Baer, O.Yu.Schmidt, and S.N. Chernikov. The main goal of this survey is to reflect some important developments in this area.